Comparative Study on The Legal Protection for Digital Wallet Users between Indonesia and South Korea - Kurniawan Sutrisno Hadi; Lucky Suryo Wicaksono (IHSA Institute, 2022)
The Digital wallet has developed rapidly in recent years. The number of users of digital wallets has been increasing significantly over several years. However, the financial accident related to digital wallets occurred and caused damage to the users. This study aims to analyze and determine the legal protection of digital wallet users for loss of e-money in Indonesia and Korea, and the legal issue from the Korean digital wallet regulation that can be harmonized in Indonesian’s regulation. This type of research is normative research using statutory and comparative approaches. The results of this study indicate that Indonesia carried out the legal protection for digital wallet users by prohibiting several actions, responsible for the loss of e-money by the provider unless the fault comes from the users, and sanctions. Korea carried out the legal protection for digital wallet users by ensuring the users safety, prohibition against electronic infringement, responsible for the loss caused by all types of electronic infringement, and sanctions. Then, several lessons can obtain to harmonize the digital wallet regulation in Indonesia, including the adoption single codified law, the responsible of the digital wallet provider and compensation for damage, and the response to the financial accident.